THE IMPACT OF SOCIAL GUIDANCE ON STUDENTS INTERPERSONAL INTERACTION SKILLS - Alisah, Marsha Jihan; Oktasari, Resti; Silvia Ar (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research explores the impact of social counseling on the interpersonal interaction skills of students. With increasing demands for effective communication and social adaptation in academic and professional settings, the development of interpersonal skills is crucial for student success. Social counseling, which provides support and guidance through structured interventions, is believed to enhance students' ability to interact effectively with peers, faculty, and others in their social environments. The study employs a mixed-methods approach, combining pre- and post-counseling assessments with qualitative interviews to assess changes in communication, empathy, conflict resolution, and cooperation. Results indicate that social counseling significantly improves students’ interpersonal skills, with marked improvements in communication abilities and relationship-building behaviors. The study contributes to the growing body of research on the role of counseling in educational settings and offers practical recommendations for integrating social counseling programs into student development initiatives.